P0353EFFECT OF RITUXIMAB IN PATIENTS WITH RELAPSED OR REFRACTORY PRIMARY MEMBRANOUS NEPHROPATHY. (6th June 2020) - Akyildiz, Arif; Uludag, Omer; Mirioglu, Safak; Ucar, Ali Riza; Demir, Erol; Caliskan, Yasar Kerem; Ozluk, Yasemin; Turkmen, Aydin; Sever, Mehmet Sukru; Yazici, Halil
Abstract: Background and Aims: Membranous nephropathy (MN) is the most common cause of glomerulonephritis in non-diabetic adults. B-cell dysfunction is an important pathway involved in pathogenesis. We, therefore, investigated effects of rituximab (RTX) on the outcome of patients with relapsed or refractory primary MN. Method: In this retrospective analysis, 48 patients with primary MN were evaluated. Patients, who had relapsed or refractory biopsy-proven disease, with a nephrotic-range proteinuria despite at least six months of prior immunosuppressive therapy using corticosteroids, calcineurin inhibitors or mycophenolic acid derivatives, which were used according to KDIGO guidelines. All patients received at least 2 doses of 375 mg/m2 of RTX. Proteinuria and serum albumin levels of the patients were recorded at baseline, and 3, 6, 12, 18 and 24 months. Results: Of 48 patients who participated in this study, 27(56.3%) were male. Mean age was 45.3±17.2 years. Results of serum anti-phospholipase-A2-receptor (PLA2R) were available in 31 patients, 23 of whom (74%) were positive. Proteinuria levels at 3, 6, 12, 18, and 24 months after treatment with RTX showed a significant decrease when compared to baseline (p<0.05) (Figure 1): From 7±3.5 g/24h at baseline to 2.6±2.4 g/24h at 12 months. Serum albumin levels at 3, 6, 12, 18, and 24 months after RTX significantly increased compared to baseline values (p<0.05) (Figure 2): From 2.97±0.76 g/dl at baseline to 3.88±0.67 g/dl at 12 months. Conclusion: Treatment with RTXiseffective in patients suffering from relapsed or refractory primary MN.